1999
DOI: 10.5194/hess-3-409-1999
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemsitry of montane springs and their influence on streams in the Cairngorm mountains, Scotland

Abstract: Abstract. Springs are important groundwater discharge points on the high altitude (>800m) plateaux of the Cairngorm mountains, Scotland and form important wetland habitats within what is often a dry, sub-arctic landscape. The hydrogeochemistry of a typical spring in the Allt a'Mharcaidh catchment was examined between 1995-98 in order to characterise its chemical composition, identify the dominant controls on its chemical evolution and estimate groundwater residence time using 18O isotopes. Spring water, sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…However, as the Sgurr Beag and Dalvorar examples show, this does not seem to occur, presumably because most snowmelt leaves the catchments as surface water. Even on the high massif of the Cairngorm Mountains to the north of Braemar, where up to 40 percent of precipitation may fall as snow, the most depleted composition sampled from a spring at 970 m was -9.7‰ (Soulsby et al, 1999), which conforms reasonably well with the Braemar altitude effect quantified above. This suggests the most depleted, reasonably well-mixed groundwater that could be expected in the British Isles under today's climatic conditions would have a δ 18 O no more negative than about -10‰.…”
Section: Altitude Effectssupporting
confidence: 69%
See 1 more Smart Citation
“…However, as the Sgurr Beag and Dalvorar examples show, this does not seem to occur, presumably because most snowmelt leaves the catchments as surface water. Even on the high massif of the Cairngorm Mountains to the north of Braemar, where up to 40 percent of precipitation may fall as snow, the most depleted composition sampled from a spring at 970 m was -9.7‰ (Soulsby et al, 1999), which conforms reasonably well with the Braemar altitude effect quantified above. This suggests the most depleted, reasonably well-mixed groundwater that could be expected in the British Isles under today's climatic conditions would have a δ 18 O no more negative than about -10‰.…”
Section: Altitude Effectssupporting
confidence: 69%
“…In Britain, the most enriched sample found during this survey had a δ 18 O value of -1.3‰, while the most depleted value reported is -10.6‰ (Soulsby et al, 1999). This range of ~9‰ is about double that measured for groundwaters (see below).…”
Section: General Backgroundmentioning
confidence: 73%
“…Similar residence times have also been estimated in for baseflows, borehole waters or springs in upland environments as different as Plynlimon, Wales (Haria and Shand, 2004); Maimai in New Zealand (McGlynn at al., 2003); pre-Alpine catchments in Switzerland (Vitvar and Balderer, 1997); the Bavarian Alps, Germany (Maloszewski et al, 1983); in Japan (Asano et al, 2002) and the Catskills, USA (Vitvar et al, 2002). Whilst the mean residence times presented in this study do not give direct groundwater residence times, earlier work by Soulsby et al (1999Soulsby et al ( , 2000 in the Cairngorms estimated the mean residence times for shallow and deeper groundwater sources at 2 and 3-5 years respectively. All these studies strongly suggest the presence of long tails in residence time distributions in such mountainous catchments (Kirchner et al, 2000).…”
Section: Discussionmentioning
confidence: 57%
“…The model had some success in simulating the chemistry during high and moderate flows, but was less successful during base flow periods. Subsequently, geochemical tracer studies of groundwater in boreholes and emerging from springs identified the important contribution of groundwater to the catchment response during both high and low flows (Jenkins et al, 1994;Soulsby et al, 1998Soulsby et al, , 1999. Increasingly, the complexity of the catchment response, in terms of intra-storm and inter-annual variation, has become apparent through the use of mixing models, both during individual events and over the hydrological year (Jenkins et al, 1994;Soulsby et al, 1998).…”
Section: Introductionmentioning
confidence: 99%